Gamma-tubulin in chicken erythrocytes: changes in localization during cell differentiation and characterization of cytoplasmic complexes - Linhartová, Irena; Novotná, Bozena; Sulimenko, Vadym; Dráberová, Eduarda; Dráber, Pavel (Developmental dynamics, 2002)
The mechanism of marginal band (MB) formation in differentiating erythroid cells is not fully understood, and the proteins involved in nucleation of MB microtubules are largely unknown. To gain insights into the function of gamma-tubulin in MB formation, we have followed its distribution in developing chicken erythrocytes and characterized soluble forms of the protein. In early stages of erythroid cells differentiation, gamma-tubulin was present in microtubule-organizing centers, mitotic spindles, as well as on MB. Its subcellular localization changed in the course of differentiation, and in postnatal peripheral erythrocytes gamma-tubulin was found only in soluble forms. After cold-induced depolymerization gamma-tubulin in erythroid cells formed large clusters that were not observed in matured cells, and re-growth experiments demonstrated that gamma-tubulin was not present in distinct nucleation structures at the cell periphery. Soluble gamma-tubulin formed complexes of various size and large complexes were prone to dissociation in the presence of high salt concentration. Interaction of gamma-tubulin with tubulin dimers was revealed by precipitation experiments. gamma-Tubulin occurred in multiple charge variants whose number increased in the course of erythrocyte differentiation and corresponded with decreased binding to MB. The presented data demonstrate for the first time that gamma-tubulin is a substrate for developmentally regulated posttranslational modifications and that the binding properties of gamma-tubulin or its complexes change during differentiation events.
Keywords: buněčná diferenciace; Macromolecular Substances; Chickens; Biopolymers; Erythrocytes; Protein Binding; biopolymery; nízká teplota; rozpustnost; Tubulin; Microtubules; stárnutí erytrocytů; makromolekulární látky; zvířata; Vimentin; Protein Processing, Post-Translational; posttranslační úpravy proteinů; Cold Temperature; kuřecí embryo; Subcellular Fractions; mikrotubuly; Chick Embryo; kur domácí; izoelektrický bod; organely; Cell Differentiation; tubulin; vazba proteinů; erytrocyty; Erythrocyte Aging; Solubility; Isoelectric Point; Animals; subcelulární frakce; Organelles; vimentin